A historical appraisal of the tropical forages collection conserved at CIAT - Schultze-Kraft, Rainer; Peters, Michael; Wenzl, Peter (Bioversity International and the International Center for Tropical Agriculture, 2020)
A report on the tropical forage germplasm collection conserved in the CIAT genebank is presented. Emphasis is firstly on the assembling of the collection during 1972−1993 through about 70 major and minor collecting missions in tropical America, Africa and Southeast Asia. Along with introductions from existing collections, currently some 1,600 accessions of 134 grass species and 21,000 accessions of 637 legume species are being maintained. Secondly, information on the utilization of the collection, with emphasis on cultivar development based on selection of accessions from the CIAT collection, is presented. Worldwide, a total of 44 grass and 34 legume cultivars derived from germplasm maintained at CIAT are reported. Information on germplasm distribution and knowledge sharing during the last four decades is also presented as well as a brief discussion on future needs.